1993
DOI: 10.1088/0957-0233/4/7/001
|View full text |Cite
|
Sign up to set email alerts
|

The tin dioxide gas sensor

Abstract: An introduction to the tin dioxide (SnO,) ceramic gas sensor and its electrical characterization is presented, followed by details of some methods of active material preparation. Problems of sensitivity, selectivity and their modification are then considered. The basic measurand is the conductance of the sensor, which means that the active material must always bridge a pair of electrodes; it must also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(115 citation statements)
references
References 15 publications
2
108
0
5
Order By: Relevance
“…Moreover, it must be taken into account the temperature dependence of mobility. Independent on considering the evaluated crystallite sizes or the metallurgical grains as the scattering unit, the grain boundary scattering is the dominant mechanism and the depletion layer may become as large as half of the crystallite 28 . The mobility due to grain boundary scattering has the general form:…”
Section: Low Temperature Electrical Characterization Of Thin Filmsmentioning
confidence: 99%
“…Moreover, it must be taken into account the temperature dependence of mobility. Independent on considering the evaluated crystallite sizes or the metallurgical grains as the scattering unit, the grain boundary scattering is the dominant mechanism and the depletion layer may become as large as half of the crystallite 28 . The mobility due to grain boundary scattering has the general form:…”
Section: Low Temperature Electrical Characterization Of Thin Filmsmentioning
confidence: 99%
“…3.1 Properties, structures, and applications of SnO 2 As an n-type semiconductor with a large band gap (E g = 3.6 eV at 300 K), SnO 2 has been studied extensively for applications in transparent conducting electrodes, lithium ion batteries and gas sensors (Watson et al, 1993). Specifically, because SnO 2 exhibits high sensitivity for detecting CO and NO x gases, vigorous studies on SnO 2 -based gas sensors have been undertaken (Watson et al, 1993).…”
Section: Sno 2 Nanobelts and Nanowires Under High Pressuresmentioning
confidence: 99%
“…Specifically, because SnO 2 exhibits high sensitivity for detecting CO and NO x gases, vigorous studies on SnO 2 -based gas sensors have been undertaken (Watson et al, 1993). In these studies, SnO 2 in orthorhombic structures was found to exhibit better sensitivity for specific gases than the tetragonal rutiletype structure (Arbiol et al, 2008;Sangaletti et al, 1997).…”
Section: Sno 2 Nanobelts and Nanowires Under High Pressuresmentioning
confidence: 99%
“…Semiconductor gas sensors on the base of nanoscale SnO 2 films are manufactured (Evdokimov et al, 1983;Buturlin et al, 1983b;Watson et al, 1993). The possibility of tin dioxide layers to change their electrical conductivity upon adsorption of gases due to the reactions of reduction and oxidation, is used (Bakin et al, 1997;Srivastava, R. et al, 1998a;Jiang et.al., 2002;Vigleb, 1989).…”
Section: Introductionmentioning
confidence: 99%